Neurosteroids as Neuromodulators in the Treatment of Anxiety Disorders - Longone, Patrizia; di Michele, Flavia; D'Agati, Elisa; Romeo, Elena; Pasini, Augusto; Rupprecht, Rainer (Frontiers in Endocrinology, 2011)
Anxiety disorders are the most common psychiatric disorders. They are frequently treated with benzodiazepines, which are fast acting highly effective anxiolytic agents. However, their long-term use is impaired by tolerance development and abuse liability. In contrast, antidepressants such as selective serotonin reuptake inhibitors (SSRIs) are considered as first-line treatment but have a slow onset of action. Neurosteroids are powerful allosteric modulators of GABAA and glutamate receptors. However, they also modulate sigma receptors and they are modulated themselves by SSRIs. Both pre-clinical and clinical studies have shown that neurosteroid homeostasis is altered in depression and anxiety disorders and antidepressants may act in part through restoring neurosteroid disbalance. Moreover, novel drugs interfering with neurosteroidogenesis such as ligands of the translocator protein (18 kDa) may represent an attractive pharmacological option for novel anxiolytics which lack the unwarranted side effects of benzodiazepines. Thus, neurosteroids are important endogenous neuromodulators for the physiology and pathophysiology of anxiety and they may constitute a novel therapeutic approach in the treatment of these disorders.